Perilaku Agresif Pada Pecandu Alkohol - Prabowo, Andika Guruh, Dr. Wiwien Dinar Pratisti M.Si (2016)
Aggressive behavior is a behavior intended to hurt and harm to other people. Aggressive behavior can cause harm to other people or the individuals themselves. One of the factors that affect aggressive behavior are consuming alcoholic beverages. Alcoholic beverages are drinks that contain similar materials or etanol and ethyl alcohol is a kind of psychoactive drug that can affect the physical and psychological for the drinker. Excessive consumption of alcoholic beverages will damage the organ performance and damage behavior. Purpose of this study was to find, understand and verify aggressive behavior in alcoholics. This study uses a qualitative method. Informants in this study were selected by purposive sampling with characteristics that belong to an alcoholic, had consumed alcoholic beverages for 2 years with the intensity of consuming alcoholic beverages two to three times a week. The results of this study indicate that 1) the aggressive behavior that is common among alcoholics is to say harsh words with friends and speaking in a high tone. 2) The purpose of consuming alcoholic beverages is a social relation, alcohol dependence, and escape from problems. 3) The more often people consuming alcoholic beverages, the more often behave aggressively. 4) individuals who consume alcoholic beverages are aged less than 30 years of aggressive behavior than individuals who consume alcoholic beverages over the age of 30 tahun.5) The level of education does not affect aggressive behavior. 6) The family members are addicted to alcoholic beverages did not affect aggressive behavior displayed by individuals. 7) When not consume alcoholic beverages, people will turn into individual closed, indifferent to others and less confident in social skills. 8) The higher the interaction between individuals who together frequently consume alcoholic beverages reduces the risk of physychaly aggresive behavior.